The use of acoustic emissions technique in the monitoring of fracturing in concrete using soundless chemical demolition agent (Fracture and Structural Integrity, 2019)
Soundless chemical demolition agents (SCDAs) have been used during the last decades in the demolition of boulders and concrete structures as well as in open-surface and sub-surface rock excavation, as an alternative to the use of explosives posing safety risks. However, the knowledge of the governing fracture mechanisms in brittle materials is rather limited. In the present work, we thoroughly investigate the use of the acoustic emission technique to study the SCDA-induced fracture process in concrete blocks. Energy-related features and waveform parameters of the recorded AE activity are correlated to the fracture mode of the concrete where a quasi-static behavior is observed. Monitoring of the progressive fracture is also achieved by the 3D localization of the AE sources. The distribution of the inter-event times of the recorded hits is further analyzed in the context of non-extensive statistical physics.
Keywords: Acoustic emissions; Fracture; Soundless chemical demolition agent; Concrete; Non-extensive statistical physics; Tsallis entropy